PERAN PEMERINTAH DALAM MENGEMBANGKAN KOTA HIJAU (GREEN GOVERNMENT) DI KOTA MAKASSAR - Nur Ichsan Amin; Akhir Saleh (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2022)
Referring to Law No. 26 of 2009 concerning green open space, ideally the area of green open space is 30% ofthe total area calculated from the area of the city as a whole, so it seems that the Makassar city governmenthas problems in meeting the demands of developing green open space towards a green city. What is expected(Green government), there are several basic assumptions that become references, including the level ofpublic awareness that is still very low to carry out reforestation independently and voluntarily, in additionto the absence of enforcement of rules through regional regulations related to the urgency of reforestationarrangements as per the Regional Regulation. No. 4 of 2015 concerning the Makassar City Spatial Plan2015-2035 which has not been implemented properly, not to mention one of the tough challenges faced inrealizing Makassar as a Green city is the incessant development of infrastructure in several road expansions.is a demand for the needs of the community, even though they have to sacrifice trees or even green openspaces that have existed before, both on the median road and on the road and even city parks that havea function as a buffer for urban green lanes. In such conditions, the role of the government becomes verydominant in determining the direction of city development towards the coveted green city.